2010
DOI: 10.1108/01443331011033328
|View full text |Cite
|
Sign up to set email alerts
|

Economic inequality and poverty: where do we go from here?

Abstract: Purpose-The paper aims to compare applied social policy approaches to child poverty and economic inequality, the latter being mainly operationalised in the UK in terms of social mobility. Design/methodology/approach-The paper considers the theoretical stance underpinning New Labour's approach towards social policy, with particular reference to ''individualisation'', and reviews Government strategies towards tackling poverty and economic inequality. Findings-Despite a decade of unprecedented investment, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Such a notion of youth non-engagement or disengagement has emphasized more the quantity side of the picture, that is, minimization of the number of NEY and maximization of the number of engaged youth. If the quality side really matters, employment sustainability issues, such as jobs without training and workplace participation (Lawy et al, 2010;Gronkvist and Largerlot, 2009), work engagement (Taipale et al, 2011), vicious cycle of "low pay, no pay" of youth IJSSP 32,7/8 transitions (MacDonald and Marsh, 2009;Smith, 2010), and measures taken to keep young people in employment with job retention and advancement schemes (MacDonald, 2008), and critique on normative ideas underpinning welfare and activation measures for young people (Wong and Chiu, 2005;Yu, 2008), would surely be taken into consideration.…”
Section: Emergence Of Neymentioning
confidence: 99%
“…Such a notion of youth non-engagement or disengagement has emphasized more the quantity side of the picture, that is, minimization of the number of NEY and maximization of the number of engaged youth. If the quality side really matters, employment sustainability issues, such as jobs without training and workplace participation (Lawy et al, 2010;Gronkvist and Largerlot, 2009), work engagement (Taipale et al, 2011), vicious cycle of "low pay, no pay" of youth IJSSP 32,7/8 transitions (MacDonald and Marsh, 2009;Smith, 2010), and measures taken to keep young people in employment with job retention and advancement schemes (MacDonald, 2008), and critique on normative ideas underpinning welfare and activation measures for young people (Wong and Chiu, 2005;Yu, 2008), would surely be taken into consideration.…”
Section: Emergence Of Neymentioning
confidence: 99%
“…The operation of Microfinance can only thrive if the repayment schedule is met promptly by the customers. Empirical studies have shown that loan repayment is determined by the quality of the beneficiaries and other factors like education, distance of the lender to the customer's business, amount of loan, duration of the loan, gender and sanction threat to the borrowers (Roslan & Abd Karim, 2009;N. Smith, 2010;Tang, 2002).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The operation of Microfinance can only thrive if the repayment schedule is met promptly by the customers. Empirical studies have shown that loan repayment is determined by the quality of the beneficiaries and other factors like education, distance of the lender to the customer's business, amount of loan, duration of the loan, gender and sanction threat to the borrowers (Roslan & Abd Karim, 2009;Smith, 2010;Tang & Bhatt, 2002).…”
Section: Review Of Past Literaturementioning
confidence: 99%